694 IMPROVING OPIATE PRESCRIBING IN OLDER ADULTS WITH HIP FRACTURES TO COMBAT THE IATROGENIC FALLOUT. (8th March 2022) - Hudson, M A J; Atkin, J; Lumley, G; Singh, S; Varma, S; Shenoy, D; Morgan, C; Peck, G; Fertleman, M; Koizia, L
Abstract: Background: The number of opioid prescriptions in older patients has increased dramatically and it is recognised that opioids are the fourth most likely drug to cause preventable hospital admissions. The adverse effects of opioids occur more frequently in the geriatric population. Little is known about the impact of postoperative pain in older adults. NICE recommends paracetamol with additional opioids if there is insufficient postoperative pain relief. Multidisciplinary management with early and then daily physiotherapy is critical. We have assessed pre-morbid, immediate and prolonged use of opioids in patients following hip fracture. Local problem Pre-intervention analysis identified 79% (57/72) of all patients being discharged on opiates. At 4-months, 37% (17/46) of those were still using them. This represents 28% (17/61) of all patients. Methods: Analysis of all patients (excluding poly-trauma) with hip fractures over the age of 60 years admitted to St Mary's Hospital. Interventions Development of local guideline on analgesia prescribing; particularly focusing senior geriatrician led decision making. Prescribing oxycodone for first 72-hours and initially using nerve block. Avoidance of transdermal preparations and withdrawing stronger opioids prior to discharge. Clear instructions for GP's on a stop date and need for community review. Patient information leaflet dispensed with all discharge opioid prescriptions. Results: Post-intervention cycle; 17% (11/63) of patients were taking prescribed opioids prior to admission (similar to the pre-cohort). 52% (33/63) were discharged on opiates, down from 79%. At 4-months, of those discharged on opioids, 30% (9/30) were still using them; lower than in the first cycle (37%). Overall reduction from 28% to 16% of patients on opioids at 4-months. Conclusion: The use of specific hip fracture analgesia guideline, senior geriatrician decision-making and support to community colleagues can reduce in-patient and community opiate prescribing, and stem the growing problem of opioid addiction, misuse and iatrogenic re-admission.